Impact of remnant cholesterol on short-term mortality in acute decompensated heart failure: cohort study evidence from Jiangxi, China - Jian, Guoan; Jiang, Kun; Lu, Zihao; He, Shiming; Xie, Lin; Zhang, Shuhua; Wang, Qun; Lu, Hengcheng; Xiong, Zhiyu; Wu, Zhiting; Xie, Guobo; Sheng, Guotai; et al. (Frontiers in Endocrinology, 2025)
IntroductionRemnant cholesterol (RC), a highly atherogenic lipid component, has been strongly implicated in the pathogenesis and adverse clinical outcomes of numerous cardiovascular and cerebrovascular diseases. However, its impact on short-term prognosis in patients with acute decompensated heart failure (ADHF) remains to be elucidated.MethodsThis study enrolled 2,365 patients with acute decompensated heart failure (ADHF) admitted to Jiangxi Provincial People’s Hospital from 2018 to 2024. Participants were stratified into quartiles based on RC. The primary outcome was 30-day all-cause mortality. Multivariable-adjusted Cox regression and restricted cubic spline regression were employed to analyze the association between RC and 30-day mortality in ADHF patients. Additionally, exploratory mediation analyses were performed to assess potential mediating roles of inflammation, oxidative stress, and nutritional factors in this relationship.ResultsDuring the 30-day follow-up period, 151 deaths were recorded. Mortality was significantly higher in the highest RC quartile compared to the other three groups (Q1:4.41% vs Q2:5.85% vs Q3:5.93% vs Q4:9.18%). After full adjustment for potential confounders, RC demonstrated a significant linear positive association with 30-day mortality in ADHF patients [Hazard ratio: 1.16 (1.05, 1.28)]. Compared with those in the lowest quartile, patients in the highest RC quartile had a 76% increased risk of 30-day mortality. Further subgroup analyses demonstrated that ADHF patients with comorbid hypertension, coronary heart disease, and reduced ejection fraction had a significantly higher 30-day mortality risk than those without these conditions. DiscussionThis Chinese cohort study reveals a dose-dependent relationship between RC and 30-day mortality in ADHF patients, particularly exacerbated in those with hypertension, coronary heart disease, or reduced ejection fraction.